Integration of Lean Six Sigma and Ergonomics in Internal Logistics in the Supply Chain – A Systematic Literature - Virarey Mayang; Markus Hartono; Amelia Santoso (Jurnal Sistem Teknik Industri, 2024)
Today's most significant challenge facing the industry is delivering good quality products quickly, at the lowest possible cost, and flexibly in meeting demand. In terms of timing accuracy, companies must have good internal logistics, one of which is good warehouse management. Productivity in warehouses can be achieved by improving efficiency in warehouse operations, thus resulting in a faster response to customer requests. In improving productivity, it is necessary first to identify unexpected activity. This study demonstrates the importance of applying Lean Six Sigma (LSS) in Supply Chain Management (SCM), particularly internal logistics in the warehouse area, by linking the ergonomics principle with the systematic literature review approach. LSS and ergonomics are mutually complementary methodologies to meet the challenges of SCM in order to have a competitive advantage in business.